Effects of Nozzle Arrangement Strategies on Spray Uniformity in Soybean–Maize Intercropping - Wei Zhong; Wanting Yang; Yalong Li; Guanqun Wang; Xiang Dong; Mingxiong Ou; Weidong Jia; Xiaowen Wang (Agronomy)
Soybean–maize intercropping involves the simultaneous planting of maize and soybean. Compound planting sprayers are equipped with a dual-spraying system, particularly for herbicide application, where isolation between crops is essential. To isolate the spraying, it is necessary to select appropriate nozzles that minimize the interference between spray boundaries while ensuring spray uniformity. This study focuses on soybean–maize intercropping systems and investigates the variation patterns of spray boundary under different nozzle arrangement types. Eccentric nozzles (i.e., spray pattern is asymmetric fan-shaped) and fan-shaped nozzles (i.e., spray pattern is symmetric fan-shaped) were evaluated at a working pressure of 0.3 MPa. The results showed that the eccentric nozzle achieved a coefficient of variation (CV) of 0.57 and a compactness of 0.43, while the fan-shaped nozzle had a CV of 0.50 and a compactness of 0.52. This indicates the eccentric nozzle maintains uniformity with a narrower boundary. In addition, this validation was conducted at 0.4 MPa, having similar observations. In soybean–maize intercropping, the maize row width ranges from 40 to 80 cm and where the maize plants exceed 2 m in height, two-eccentric nozzles are required, tested at spacing intervals of 50 cm, 70 cm, and 90 cm. At 0.3 MPa, the CV reached its minimum value (0.3) at a spacing of 70 cm. Additionally, the spray volume on the eccentric nozzle side decreased as the spacing increased. The soybean row width ranges from 160 to 240 cm, requiring eccentric nozzles on both sides and a fan-shaped nozzle in the middle. The spacing between the eccentric and fan-shaped nozzles is chosen to be 50, 70, and 90 cm. A combination of eccentric and fan-shaped nozzles was tested at the same spacing intervals. The results showed that the CV consistently decreased with increasing spacing, and the spray volume on the eccentric nozzle side also declined. Overall, the optimal nozzle configuration for maize zones is two eccentric nozzles at a spacing of 70 cm, while for soybean zones, combining an eccentric nozzle with a fan-shaped nozzle at a spacing of 90 cm effectively ensures both spray uniformity and boundary compactness when variation in windspeed and direction are ignored.